The big thaw: waters freed from cryo-cooling yield dynamic protein–ligand interactions - Stachowski, Timothy; Vanarotti, Murugendra; Nithianantham, Stanley; Jayaraman, Seetharaman; Lopez, Karlo; Fischer, Marcus (Acta crystallographica. Section A, Foundations and advances, 2022)
Abstract only